Weeds Diversity in Rubber Plant (Hevea Brasiliensis) at Perkebunan Nusantara Company, Ciamis, Indonesia - Hexa Hidayah; Ilham Noorhakim; Dwi Wibowo; Rosyid Al Hakim (PT FORMOSA CENDEKIA GLOBAL, 2022)
This research aims to analyze the diversity of weeds species in rubber plants at Perkebunan Nusantara Company, Ciamis, Indonesia. We used the survey method with line transects sampling. Weed diversity in rubber plantations was analyzed using Shannon-Wiener Index (H'), while the evenness of plants was analyzed using the Evenness Index (E'). The research results showed that 38 species from 18 weed families were found. The weed species with the highest number is Ischaemum timorense (IVI = 36.71%) as a dominant species, while the weed species with the lowest number of individuals was Cyrtococcum patens (IVI = 0.48%). Weed diversity in rubber plants has an H' = 4.66; its higher diversity value indicates a more stable community in this area.